Predictions of the LSST Solar System Yield: Near-Earth Objects, Main Belt Asteroids, Jupiter Trojans, and Trans-Neptunian Objects - Kurlander, Jacob A.; Bernardinelli, Pedro H.; Schwamb, Megan E.; Juric, Mario; Murtagh, Joseph; Chandler, Colin Orion; Merritt, Stephanie R.; Nesvorny, David; Vokrouhlicky, David; Jones, R. Lynne; Fedorets, Grigori; Cornwall, Samuel; et al. (American Astronomical Society, 2026)
The NSF-DOE Vera C. Rubin Observatory is a new 8m-class survey facility presently being commissioned in Chile, expected to begin the 10 yr long Legacy Survey of Space and Time (LSST) by the end of 2025. Using the purpose-built Sorcha survey simulator, and near-final observing cadence, we perform the first high-fidelity simulation of LSST's solar system catalog for key small body populations. We show that the final LSST catalog will deliver over 1.1 billion observations of small bodies and raise the number of known objects to 1.27E5 near-Earth objects, 5.09E6 main belt asteroids, 1.09E5 Jupiter Trojans, and 3.70E4 trans-Neptunian objects. These represent 4x -9x more objects than are presently known in each class, making LSST the largest source of data for small body science in this and the following decade. We characterize the measurements available for these populations, including orbits, griz colors, and light curves, and point out science opportunities they open. Importantly, we show that similar to 70% of the main asteroid belt and more distant populations will be discovered in the first 2 yr of the survey, making high-impact solar system science possible from very early on. We make our simulated LSST catalog publicly available, allowing researchers to test their methods on an up-to-date, representative, full-scale simulation of LSST data.